Fucosterol exerts an anti-atherosclerotic action via NF-κB and p38/Erk MAPK signaling pathways - Tiancheng Liu; Mengli Zhang; Xian Wu; Zhenxing Liu; Huan Peng; Feng Gui; Wen Xiong; Qijuan Liu; Guojun Du; Bo Liu; Chenchen Zhang; Junfeng Ma; et al. (Atherosclerosis Plus)
Background: Fucosterol is a sterol isolated from brown algae and has various biological properties, such anti-inflammatory and antidiabetic effects. In this study, we investigated the anti-atherosclerosis effects of fucosterol in vivo and in vitro. Methods: ApoE−/− mice were fed a high fat diet for 12 weeks with or without fucosterol treatment. H&E staining and Oil Red O staining were performed to detect atherosclerotic lesion and lipid content in the aorta of mice. The lipid metabolism indexes in the mouse serum were measured. Macrophage infiltration into the aortic wall was detected using immunohistochemistry of CD68. Human umbilical vein endothelial cells (HUVECs) were treated with 100 μg/mL ox-LDL to establish a cell model of atherosclerosis in vitro. The expression and protein levels of adhesion molecules and inflammatory cytokines in the aorta and HUVECs were measured using RT-qPCR and western blot, respectively. The levels of oxidative stress-related markers in the mouse serum and HUVECs were measured using corresponding detection kits. The effects of fucosterol on the viability and apoptosis of HUVECs were detected using CCK-8 and flow cytometry, respectively. The levels of NF-κB and p38/Erk MAPK pathway-related proteins in HUVECs were assessed by western blot. Results: Fucosterol reduced atherosclerotic plaques and lipid levels in apoE−/− mice. Fucosterol alleviated macrophage infiltration, inflammatory response, and oxidative stress in apoE−/− mice. The ox-LDL-induced inflammatory response, oxidative stress, and apoptosis in HUVECs were attenuated by fucosterol. Additionally, fucosterol reduced the expression of proprotein convertase subtilisin/kexin type 9 (PCSK9) in vivo and in vitro. Moreover, the ox-LDL-induced activation of the NF-κB and p38/Erk MAPK signaling in HUVECs was suppressed by fucosterol. Conclusion: The current investigation revealed that fucosterol attenuates atherosclerotic plaques in apoE−/− mice through the inhibition of hyperlipidemia, inflammation, and oxidative stress.